DESKRIPSI PELAKSANAAN PEMBELAJARAN MODEL PROBLEM BASED LEARNING MELALUI E-LEARNING PADA ASPEK KEMAMPUAN BERPIKIR KRITIS SISWA MASA PANDEMI COVID-19 - Pranto Wati; Yustina Yustina; Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to describe the supporting facilities for the implementation of learning and the relationship between problem-based learning through e-learning and students' critical thinking skills. This research is a descriptive study with a qualitative approach. The subjects of the research were students of class XI SMA Islam As-Shofa Pekanbaru. The problem based learning based of students' critical thinking skills with indicators of analyzing, synthesizing, recognizing and solving problems, concluding, and evaluating. The collection of data on critical thinking skills is a survey with observation. Based on the results of the research, SMA Islam As-shofa stated that it has adequate facilities for e-learning. Students on average have facilities in the form of hardware, software, and a learning community. It can be concluded that the implementation of learning with the Problem Based Learning (PBL) model through e-learning on the aspect of students' critical thinking skills is running well in accordance with the relationship of e-learning activities with problem based learning and has been accompanied by facilities that support adequate learning.Key Words: E-learning, Problem Based Learning, Critical Thinking, Facilities